A corrosion-resistant biomineralized film layer and its preparation method and application

By forming a tight bioCaCO3 film layer on the surface of the metal material, the problem of insufficient corrosion resistance of metal materials in the marine environment is solved, and a low-cost and environmentally friendly corrosion resistance effect is achieved.

CN119733662APending Publication Date: 2025-04-01SUZHOU ZHIKANG NEW MATERIALS TECHNOLOGY CO LTD +1

Patent Information

Application Number
CN202411947148.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Metal materials have insufficient corrosion resistance in marine environments, and the existing technology has environmental pollution problems such as high cost, regular maintenance, and organic polymer degradation.

Method used

The metal material was soaked in the protobacterial solution and cementitious agent respectively by immersion method, and the Ca2+ in the mineralized solution was used to induce the urease-producing bacteria to form a tight biological CaCO3 film layer covering the metal surface to form an organic-inorganic composite biomineralized film.

Benefits of technology

It achieves excellent corrosion resistance in marine environments, reduces the corrosion rate of metal materials, and the method is low-cost, environmentally friendly, and does not require regular maintenance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005213948030000011
    Figure HDA0005213948030000011
  • Figure HDA0005213948030000012
    Figure HDA0005213948030000012
  • Figure HDA0005213948030000013
    Figure HDA0005213948030000013
Patent Text Reader

Abstract

The present invention provides a corrosion-resistant biomineralization film layer and a preparation method and application thereof, that is, using an immersion method to immerse a metal material in a bacterial solution and a binder in sequence, first forming a biofilm, and then using urease-producing bacteria to induce Ca in the mineralization solution. 2+ A compact biological CaCO3 film layer is generated to cover the metal surface, and together with the biofilm, it forms an organic-inorganic composite biomineralization film with excellent corrosion resistance. The present application pre-treats the metal material so that it can obtain a strongly adhesive biofilm, and through the synergistic mineralization effect of the synergistic bacteria and the urease-producing bacteria, it can improve the biomineralization film formation ability while promoting the secretion of a large number of natural corrosion inhibitors; the present invention applies the MICP technology, which is widely used and highly effective in the field of geotechnical engineering, to metal materials, mainly using the urease-producing bacteria with extremely high mineralization rate in the MICP technology, so that the surface of the metal material is covered with a layer of organic-inorganic biomineralization film with excellent corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal anti-corrosion, and in particular to a corrosion-resistant biomineralization film layer and a preparation method and application thereof. Background Art

[0002] The corrosion problem of metal materials in marine environments has always been a global problem to be solved. In marine environments, commonly used anti-corrosion methods for metal materials include coating protection, cathodic protection, the use of inhibitors or the selection of corrosion-resistant materials such as stainless steel, but these common methods have more or less disadvantages such as high cost, regular maintenance, organic polymer degradation, environmental pollution, and consumption of additional energy. In addition, the marine environment is rich in corrosive bacteria such as sulfate-reducing bacteria, which can easily induce pitting corrosion in metals and accelerate corrosion. Therefore, biocorrosion of metals is also a hot topic in current research, especially in the field of corrosion resistance of metal materials in marine environments.

[0003] Microbially Induced Calcite Precipitation (MICP) is a green, efficient and low-cost foundation treatment technology that has emerged in the field of geotechnical engineering in recent years. There are many types of MICP technologies, including urease catalysis, denitrification, carbonic anhydrase catalysis, etc. The key to the mechanism of urease-catalyzed calcium carbonate deposition is that urease-producing bacteria catalyze the hydrolysis of urea to produce CO3 2- .

[0004] CN202011404277.2 discloses a steel anticorrosion method based on microbial technology. In the process of immersing the steel sheet in the bacterial solution, the microorganisms first secrete an organic layer - extracellular polymers through metabolism, which is tightly wrapped on the surface of the steel. Then, in the presence of an organic calcium source, an inorganic layer - calcium carbonate is deposited by the microorganisms, which is attached to the organic layer, thereby realizing the protective layer structure of the organic-inorganic composite layer, preventing cathode depolarizers such as oxygen from reaching the metal surface, blocking electron transfer, and achieving the effect of preventing steel corrosion. This patent only uses Bacillus powder with low mineralization efficiency, and first mixes the bacterial solution with the calcium source, that is, adopts a one-step addition sequence. This will not only cause the bacteria to combine with ions in advance, generate calcium carbonate particles in advance, and affect the combination of bacteria and calcium carbonate with materials, but also cause the high-concentration calcium source to directly contact the bacteria. The bacteria are in a high-concentration solution, which causes the bacteria to lose water inside, thereby losing activity, and then affecting the deposition of calcium carbonate.

[0005] CN202310175729.1 discloses a rapidly synthesized biomineralization coating and its preparation method and application, using microorganisms to form biofilms on the surface of metal materials and adding biomineralization nucleation solutions modified by common acidic molecules. The preparation method of this invention is to form a biofilm on the surface of the metal material, and then use the amorphous calcium carbonate in the biomineralization nucleation solution to directly bind to the anion groups of the biofilm, saving the binding time of calcium ions and carbonate ions in the initial nucleation process, and being able to quickly form a calcite crystal-type calcium carbonate structure in a shorter time. This patent first uses a mixed bacterial solution of multiple bacteria, and then uses a mineralization solution with complex components, and provides carbonate ions by directly adding sodium carbonate solution. It is also necessary to add sodium hydroxide solution to adjust the pH later, and the bacterial activity may be affected, and the operation is slightly cumbersome. Summary of the invention

[0006] Aiming at the problem that the existing metal materials have insufficient corrosion resistance under marine environment conditions, the present application proposes a corrosion-resistant biomineralization film layer and its preparation method and application, that is, using the immersion method to immerse the metal material in the original bacterial solution and the binder respectively, using urease-producing bacteria to induce Ca in the mineralization solution 2+ A compact biological CaCO3 film is formed to cover the metal surface, forming an organic-inorganic composite biomineralization film with excellent corrosion resistance together with the biofilm.

[0007] A method for preparing a corrosion-resistant biomineralized film layer, characterized in that it comprises the following steps:

[0008] (1) Pretreatment of metal materials: Place the metal material in a phosphate buffer solution and stir it continuously at a temperature of 30-40°C for 0.5-1h, and use it after natural drying.

[0009] (2) Preparation of the original bacterial solution: inoculate the urease-producing bacteria into a suitable culture medium, and culture at a temperature of 25-35° C. and a rotation speed of 150-250 rpm for 18-30 hours to obtain a urease-producing bacterial solution; mix the synergistic bacterial strain powder with deionized water and stir to obtain the synergistic bacterial solution; mix the urease-producing bacterial solution with the synergistic bacterial solution to obtain the original bacterial solution; the ratio of the urease-producing bacterial solution to the synergistic bacterial solution is 1:(0.1-0.3);

[0010] (3) Preparation of the binder: mixing the calcium source, urea and deionized water at room temperature;

[0011] (4) Formation of the film layer: the pretreated metal material is immersed in the bacterial solution for 5-10 minutes, and then the binder of step (3) is added, mixed to form a mineralizing solution, and then allowed to stand, and the metal material is covered with a corrosion-resistant biomineralized film layer;

[0012] The phosphate buffer contains calcium chloride, and the concentration of calcium chloride in the phosphate buffer is 0.1-0.8 mmol / L.

[0013] The phosphate buffer is selected from any one of sodium phosphate buffer and potassium phosphate buffer, and has a pH of 7.8-9.0.

[0014] The urease-producing bacteria can be selected from any one of Bacillus pasteurianus, Bacillus lentus and Bacillus sphaericus; the concentration of the urease-producing bacteria is: 1-2 ml of urease-producing bacteria liquid is added to every 100 ml of culture medium; the OD600 of the urease-producing bacteria liquid is 1.0-1.9.

[0015] The formula of the above culture medium is: 1-3g yeast powder, 1-2g tris (tris), and 0.5-1.5g ammonium sulfate per 100ml deionized water; and the prepared culture medium needs to be sterilized at a temperature of 110-130°C for 20-40min.

[0016] The above-mentioned synergistic bacteria can be selected from any one of Bacillus subtilis, Bacillus coli, and Pseudomonas aeruginosa; the mass ratio of the above-mentioned synergistic bacteria powder to deionized water is (4-10):100.

[0017] In the above step (3), the mass ratio of the calcium source, urea and deionized water is (4-6):(2-4):100; the above calcium source is a soluble calcium salt, and the soluble calcium salt is any one of calcium nitrate, calcium acetate and calcium chloride.

[0018] The volume ratio of the above-mentioned original bacterial liquid to the binder is 1:(0.5-2).

[0019] The static condition of the above step (4) is immersion at 10-35° C. for 1-9 days. Too low static environment temperature affects the bacterial activity and thus affects the formation of the corrosion-resistant biomineralized film layer.

[0020] The corrosion-resistant biomineralized film layer is used in the field of metal material corrosion resistance, and is particularly suitable for the field of metal corrosion resistance in marine environments.

[0021] Compared with the prior art, this application has the following advantages:

[0022] (1) Phosphate buffer can provide a suitable acid-base environment for the surface of metal materials, protecting biological macromolecules such as proteins and nucleic acids inside cells from damage. At the same time, phosphate buffer can form a layer of phosphate film on the surface of metal materials, which not only improves the corrosion resistance of metal materials, but also helps the attachment of biomineralized films.

[0023] (2) Adding a small amount of calcium chloride to the phosphate buffer can not only improve the salt concentration of the buffer, but also provide a more suitable living environment for bacterial cells. At the same time, calcium ions, as a cofactor of bacterial metabolism, can improve the growth and mineralization efficiency of bacteria. In addition, introducing a small amount of calcium source on the surface of the metal material in advance allows bacteria to combine with metal ions and a small amount of calcium ions in advance during the coating process. After the bacteria decompose urea to produce carbonate ions, the carbonate ions can directly combine with the calcium ions on the bacteria, thereby improving the mineralization rate of the mineralized layer and the density and stability of the film layer.

[0024] (3) Synergistic bacteria can secrete a large amount of corrosion inhibitors such as aspartic acid and glutamic acid, and further improve the corrosion resistance of metal materials through the synergistic effect of multiple mechanisms. At the same time, the metabolites or sticky substances (such as polysaccharides) secreted by the synergistic bacteria help to improve the structure and adhesion of the mineralized film. Different bacteria can also form a collaborative network in the membrane to enhance the stability and durability of the membrane in complex environments. In addition, the synergistic bacteria contain other mineralizing enzymes such as carbonic anhydrase, which can synergize with urease-producing bacteria to optimize the calcium carbonate deposition rate. However, if the number of synergistic bacteria is too large, it will inhibit the growth and reproduction of the dominant bacteria, urease-producing bacteria, thereby reducing the effectiveness of the biomineralization layer and reducing the corrosion resistance.

[0025] (4) Compared with other biological or chemical technologies for preparing biomineralized corrosion-resistant film layers, the present invention utilizes pretreatment liquid to enhance biological action, urease-producing bacteria to decompose urea for rapid mineralization, and the synergistic effect of synergistic mineralization enzymes secreted by synergistic bacteria and natural corrosion inhibitors, thereby achieving the rapid synthesis of a natural, stable, dense, gelled biomineralized film layer.

[0026] The mechanism of action of this application is mainly: strong adhesion biofilm, high enzyme activity mineralization ability, corrosion inhibitors secreted in metabolism, consumption of corrosive substances in the environment, and construction of bionic organic-inorganic hybrid film on the metal surface; the present invention applies the MICP technology, which is widely used and highly effective in the field of geotechnical engineering, to metal materials, mainly using urease-producing bacteria with extremely high mineralization rate in the MICP technology, so that the surface of the metal material is covered with an organic-inorganic biomineralized film with excellent corrosion resistance. Compared with the traditional corrosion resistance methods of metals in marine environments, this method has a lot of advantages and is an important emerging topic in the field of metal corrosion protection, with great research prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a real picture of the beaker after the iron sheet of Example 1 is immersed in the mineralizing liquid in the beaker for 1 day;

[0028] Figure 2 The macroscopic morphology of the iron sheet in Example 1 after being immersed in the mineralizing solution for 0 days, 1 day, and 7 days;

[0029] Figure 3This is a SEM image of the surface of the iron sheet in Example 1 after being immersed in the mineralizing liquid for seven days;

[0030] Figure 4 This is a SEM image of the surface of the iron sheet of Example 1 after being immersed in the mineralizing solution for seven days and then immersed in a sodium chloride solution with a mass fraction of 3.5% for 14 days;

[0031] Figure 5 This is the XRD pattern of the iron sheet in Example 1 after being immersed in the mineralizing solution for seven days;

[0032] Figure 6 This is a graph showing the relationship between the impedance of the iron sheet and the mineralization time in Example 3;

[0033] Figure 7 This is a graph showing the relationship between the impedance of the copper sheet and the mineralization time in Example 4;

[0034] Figure 8 The surface morphology of the iron sheet of Example 1 after being immersed in the mineralizing solution for seven days, and then immersed in the sodium chloride solution with a mass fraction of 3.5% for 2 days and 14 days is shown in real pictures, and the surface morphology of the iron sheet of Comparative Example 1 after being immersed in the sodium chloride solution with a mass fraction of 3.5% for 2 days and 14 days is shown in real pictures;

[0035] Fig. 9 The surface morphology of the iron sheet of Example 2 after being immersed in the mineralizing liquid for seven days and then immersed in the sodium chloride solution with a mass fraction of 3.5% for 1 day, 2 days, 4 days, 5 days and 8 days is shown in real pictures, and the surface morphology of the iron sheet of Comparative Example 1 after being immersed in the sodium chloride solution with a mass fraction of 3.5% for 1 day, 2 days, 4 days, 5 days and 8 days is shown in real pictures;

[0036] Fig.10 The macroscopic morphology of Comparative Example 2 and Example 3;

[0037] Fig.11 This is a SEM image of the iron sheet of Comparative Example 4 after being immersed in the mineralizing solution for seven days;

[0038] Fig.12 This is the protein distribution diagram of the original bacterial solution in Example 5;

[0039] Fig.13 This is a protein composition analysis diagram of the original bacterial solution in Example 5;

[0040] Fig.14 The figure is a graph showing the change of environmental dissolved oxygen with immersion time in Example 6 and Comparative Example 1;

[0041] Fig.15 The impedance comparison diagram of comparative example 4 and embodiment 1;

[0042] Fig.16 This is the SEM image of the iron sheet surface of Comparative Example 5;

[0043] Fig.17 This is the SEM image of the iron sheet surface of Comparative Example 6;

[0044] Fig.18 This is the SEM image of the iron sheet surface in Comparative Example 7. DETAILED DESCRIPTION

[0045] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] The urease-producing bacteria used in the following examples is Bacillus pasteurianus, and the synergistic bacteria is Pseudomonas aeruginosa.

[0047] Embodiment 1:

[0048] Add 4 g of yeast powder, 3.146 g of tris, and 2 g of ammonium sulfate into a beaker, and then use deionized water and a conical flask to make the volume 200 ml to prepare a culture medium.

[0049] Seal the bottle with gauze, newspaper and rubber band, and sterilize the conical bottle and syringe in an autoclave at 121°C for 30 minutes. After sterilization, cool the bottle to 35°C in a cold bath.

[0050] (1) Pretreatment of metal materials: Place the iron sheet in sodium phosphate buffer and stir continuously for 1 h at a temperature of 35°C;

[0051] The concentration of calcium chloride in sodium phosphate buffer is 1 mmol / L.

[0052] (2) Cultivation of bacterial strains: Add 2 ml of urease-producing bacterial culture to 200 ml of culture medium, sterilize the mouth of the conical flask and gauze over the flame of an alcohol lamp, and place the flask in a shaker for shaking culture to obtain the urease-producing bacterial culture.

[0053] The shaking speed was 200 rpm, the temperature was 30°C, and the culture time was 24 h. After the culture, the OD600 was measured to be 1.5.

[0054] The synergistic bacterial strain powder and deionized water (4:100) were stirred and mixed for culture, and the supernatant was taken to obtain the synergistic bacterial solution;

[0055] The urease-producing bacterial solution was mixed with the synergistic bacterial solution (1:0.3) to obtain the original bacterial solution.

[0056] (3) Preparation of binder: Add 5.55 g of anhydrous CaCl2 and 3 g of urea into a beaker and dilute to 100 ml with deionized water;

[0057] (4) Formation of the film layer: first add 50 ml of the original bacterial solution to a beaker, immerse the treated iron sheet in the original bacterial solution, let it stand for 10 minutes, and then add 50 ml of a binder; place it in an environment of 25°C and soak for 7 days to obtain an iron sheet with a corrosion-resistant biomineralized film layer on the surface.

[0058] Result analysis:

[0059] like Figure 1 This is the situation in the beaker after soaking for one day. It can be observed that the white precipitates at the bottom are all calcium carbonate precipitates induced by urease-producing bacteria.

[0060] like Figure 2 As shown, from left to right are the original photos of the iron sheet after treatment, the photos after immersion for 1 day in step (4), and the photos after immersion for 7 days in step (4). It can be observed that in a very short time, a layer of calcium carbonate precipitation can be covered on the iron sheet; after immersion for 7 days, the mineralized film layer on the surface of the iron sheet has become relatively dense.

[0061] like Figure 3 It can be observed that after immersion for 7 days in step (4), the surface of the iron sheet is covered with a dense spherical calcite film. Because there are ammonium ions in our mineralization solution, vaterite tends to form, and vaterite is metastable and will slowly transform into a stable calcite form.

[0062] The iron sheet provided in Example 1, which had been soaked for seven days in step (4), was then soaked in a 3.5% sodium chloride solution for 14 days. Figure 4 It can be observed that the surface of the iron sheet is still covered with a dense calcium carbonate film, which effectively delays the corrosion of the iron sheet.

[0063] The XRD experimental results are shown in Figure 5 As shown, it can be observed that the film layer on the surface of the iron sheet is composed of a large amount of calcium carbonate.

[0064] Example 2

[0065] The difference between Example 2 and Example 1 is that: 3 ml of urease-producing bacteria solution is added in step (1), and the OD600 after culture is measured to be 1.8.

[0066] After Example 2 was mineralized for 7 days, it was immersed in a 3.5% by mass sodium chloride solution together with Comparative Example 2 to compare and observe the changes in appearance.

[0067] Example 3

[0068] The difference between Example 3 and Example 1 is that: 2.5 ml of urease-producing bacteria solution is added in step (1), and the OD600 measured after cultivation is 1.7.

[0069] An EIS experiment was conducted on the iron sheet to observe the change of its impedance with immersion time.

[0070] Electrochemical impedance spectroscopy test: A three-electrode system is used, the working electrode is an iron sheet covered with a biomineralized film, the counter electrode is a platinum sheet, and the reference electrode is a saturated calomel electrode. The test range is 10-2Hz-105Hz.

[0071] The results are as follows Figure 6 As shown in the figure, the larger the diameter of the semicircular curve in the Nyquist diagram, the greater the impedance of the iron sheet. Therefore, the values ​​of the horizontal and vertical coordinates covered by it can reflect the impedance to a certain extent. It can be observed that after only two days of immersion, the impedance of the iron sheet is much greater than that of the untreated original iron sheet, and after five and ten days, the impedance is far greater than that of the original iron sheet. The results show that the corrosion-resistant biomineralized film layer has excellent corrosion resistance, and within a certain range, the impedance of the iron sheet increases with the increase of mineralization time.

[0072] Example 4

[0073] The difference between Example 4 and Example 1 is that a copper sheet is used as the metal material, and the method for processing the copper sheet is the same as the method for processing the iron sheet.

[0074] The results are as follows Figure 7 As shown, the diameter of the semicircle of the curve is larger than that of the original sample, indicating that the corrosion-resistant biomineralized film layer provides corrosion resistance.

[0075] Example 5

[0076] The difference between Example 5 and Example 1 is that: 5 ml of urea solution is added in step (1), and the OD600 measured after culture is 1.6.

[0077] Distribution of membrane proteins Fig.12 As shown in the figure, it can be observed that the surface of the metal material is evenly distributed with proteins, which are derived from the extracellular polymeric substances secreted by microorganisms in the corrosion-resistant biomineralization film layer. The anionic functional groups in the extracellular polymeric substances can combine with the metal cations on the surface of the metal material to form a dense and stable natural corrosion-resistant protective layer.

[0078] The composition of protein Fig.13 As shown, it can be observed that the protein is mainly composed of aspartic acid and glutamic acid, which are natural corrosion inhibitors. This indicates that the corrosion-resistant bionic film layer of the present invention contains and can secrete natural corrosion inhibitors to inhibit corrosion.

[0079] Example 6

[0080] The difference between Example 6 and Example 1 is that: in step (1), 3 ml of urease-producing bacteria solution and 4 ml of urea solution are added, and the OD600 measured after cultivation is 1.7.

[0081] Example 7

[0082] The difference between Example 7 and Example 1 is that in step (2), the ratio of urease-producing bacteria liquid to synergistic bacteria liquid is (1:0.1).

[0083] Example 8

[0084] The difference between Example 8 and Example 1 is that in step (1), the concentration of calcium chloride in the sodium phosphate buffer is 0.1 mmol / L.

[0085] Comparative Example 1

[0086] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 only performs the pretreatment of the metal material in step (1).

[0087] The treated iron sheet is soaked in a 3.5% sodium chloride solution for 14 days; the iron sheet provided in Example 1, Example 2, and Example 6, which has been soaked for seven days in step (4), is soaked in a 3.5% sodium chloride solution for another 14 days.

[0088] The comparison results of Comparative Example 1 and Example 1 are as follows Figure 8 As shown, it can be observed that the surface of the iron sheet of comparative example 1 is completely transformed into corrosion products in a very short time. However, the biomineralized film layer on the surface of the iron sheet of embodiment 1 effectively slows down the corrosion rate of the iron sheet and provides excellent corrosion resistance.

[0089] The comparison results of Comparative Example 1 and Example 2 are as follows Fig. 9 As shown, it can be observed that Figure 8 The experimental conclusions are the same.

[0090] The comparison results of Comparative Example 1 and Example 6 are as follows Fig.14 As shown, it can be observed that the corrosion-resistant biofilm layer prepared by the present invention can consume corrosive substances in the environment through metabolic activities such as cell respiration, provide an environment with lower dissolved oxygen for metal materials, and greatly inhibit the oxidation of metal materials.

[0091] It is further verified that the corrosion-resistant biomineralized film layer successfully and rapidly prepared on the surface of the iron sheet in this embodiment has excellent corrosion resistance.

[0092] Comparative Example 2

[0093] The difference between Comparative Example 2 and Example 3 is that no immersion in bacterial solution is performed, that is, the operation of step (4) is: placing the treated iron sheet in a beaker and adding 50 ml of binder; soaking it in an environment of 25°C for 7 days to obtain an iron sheet without a biomineralized film layer on the surface.

[0094] The comparison results of Comparative Example 2 and Example 3 are as follows Fig.10 As shown, it can be observed that corrosion products are generated on the surface of the iron sheet immersed in the binder only. The reason is that due to the lack of mineralization by bacteria, the calcium chloride in the binder plays a corrosive role. However, a dense mineralized film layer is attached to the surface of the iron sheet immersed in the mineralizing solution required by the present invention.

[0095] Comparative Example 3

[0096] The difference between Comparative Example 3 and Example 1 is that the film layer formation steps are different, that is, the operation of step (4) is: first add 50 ml of original bacterial solution to a beaker, immediately add 50 ml of binder, mix to form a mineralized solution, directly immerse the treated iron sheet in the mineralized solution, place it in an environment of 25°C and soak for 7 days to obtain an iron sheet with a microbial mineralized film layer on the surface.

[0097] The results of Comparative Example 3 are as follows Fig.11 As shown, the surface is full of long and thin bacteria, but there is no further deposition of calcium carbonate on the bacteria, and the calcium carbonate film layer below has obvious cracks, which is different from the present invention. Figure 3 and Figure 4 A large amount of calcium carbonate is deposited on the surface, and the film layer below is also denser. Comparative Example 3 first mixes the bacterial solution with the calcium source, that is, adopts a one-step addition sequence. Doing so will not only cause the bacteria to combine with ions in advance, generate calcium carbonate particles in advance, and affect the combination of bacteria and calcium carbonate with the material, but also cause the high-concentration calcium source to directly contact the bacteria. The bacteria are in a high-concentration solution, causing the bacteria to lose water inside, thereby losing activity, and further affecting the deposition of calcium carbonate.

[0098] Comparative Example 4

[0099] The difference between Comparative Example 4 and Example 1 is that the original bacterial liquid of Comparative Example 4 only contains urease-producing bacterial liquid, and no synergistic bacterial liquid is used.

[0100] The results are as follows Fig.15 As shown, it can be observed that the impedance arc radius of Comparative Example 4 is much smaller than that of Example 1, indicating that the synergistic bacterial solution and the urease-producing bacterial solution can greatly improve the corrosion resistance of the film layer through multi-mechanism synergistic effects.

[0101] Comparative Example 5

[0102] The difference between Comparative Example 5 and Example 1 is that the ratio of the urease-producing bacteria liquid to the synergistic bacteria liquid in Comparative Example 5 is 1:0.5.

[0103] Comparative Example 5 Results Fig.16As shown in the figure, it can be observed that when the content of the synergistic bacterial solution is too high, the bacteria and mineralization products on the surface of the iron sheet are unevenly distributed, resulting in a decrease in the density and uniformity of the mineralized layer. The reason is that when the content of the synergistic bacterial solution is too high, it will affect the growth and reproduction of urease-producing bacteria, resulting in a decrease in the status and role of the dominant bacteria urease-producing bacteria, thereby reducing the efficiency of the mineralized layer.

[0104] Comparative Example 6

[0105] The difference between Comparative Example 6 and Example 1 is that the sodium phosphate buffer used for pretreatment of the metal material in Comparative Example 6 does not contain calcium chloride.

[0106] Comparative Example 6 Results Fig.17 As shown, it can be observed that when the pre-treated sodium phosphate buffer does not contain calcium chloride, the uniformity of the film layer is significantly reduced. The reason is that when a small amount of calcium chloride is lacking for pre-treatment, the bacteria cannot combine with a small amount of calcium ions in advance, and can only combine with metal ions in advance to attach to the surface of the material. As a result, when the binder is injected, the bacteria attached to the surface of the material cannot be effectively combined with calcium ions. In addition, the salt concentration in the buffer is not the most suitable salt concentration for bacterial growth and development, resulting in reduced bacterial activity.

[0107] Comparative Example 7

[0108] The difference between Comparative Example 7 and Example 1 is that the sodium phosphate buffer used for pretreatment of the metal material in Comparative Example 7 contains calcium chloride at a concentration of 1 mmol / L.

[0109] Comparative Example 7 Results Fig.18 As shown in the figure, it can be observed that when the calcium chloride concentration in the sodium phosphate buffer treated is too high, corrosion products will be dispersed on the surface of the film layer. The reason is that when the calcium chloride content is too high, the material will be corroded prematurely. Moreover, too high salt concentration will also affect the activity of bacteria. In addition, if the calcium ion content that combines with bacteria in advance is too high, the bacteria will be surrounded by calcium ions, affecting the intake of urea and nutrients, and then affecting the formation of the mineralized layer and the growth and development of bacteria.

[0110] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a corrosion-resistant biomineralized film, characterized in that: The following steps are involved: (1) Pretreatment of metal materials: Place the metal materials in a phosphate buffer solution and stir continuously while maintaining the temperature at 30-40°C; (2) Preparation of the original bacterial solution: inoculate the urease-producing bacteria into a suitable culture medium, and culture at a temperature of 25-35° C. and a rotation speed of 150-250 rpm for 18-30 hours to obtain a urease-producing bacterial solution; mix the synergistic bacterial strain powder with deionized water and stir to obtain the supernatant to obtain the synergistic bacterial solution; mix the urease-producing bacterial solution with the synergistic bacterial solution to obtain the original bacterial solution; (3) Preparation of the binder: mixing the calcium source, urea and deionized water at room temperature; (4) Formation of the film layer: the pretreated metal material is immersed in the bacterial solution for 5-10 minutes, and then the binder of step (3) is added, mixed to form a mineralizing solution, and then allowed to stand, and the metal material is covered with a corrosion-resistant biomineralized film layer; The phosphate buffer contains calcium chloride, and the concentration of calcium chloride in the phosphate buffer is 0.1-0.8 mmol / L; The dosage ratio of the urease-producing bacteria liquid to the synergistic bacteria liquid is 1:(0.1-0.3).

2. The preparation method according to claim 1, characterized in that: The phosphate buffer is selected from any one of sodium phosphate buffer and potassium phosphate buffer, and has a pH of 7.8-9.

0.

3. The preparation method according to claim 1, characterized in that: The urease-producing bacteria can be selected from any one of Bacillus pasteurianus, Bacillus lentus and Bacillus sphaericus; the concentration of the urease-producing bacteria is: 1-2 ml of urease-producing bacteria liquid is added to every 100 ml of culture medium; the OD600 of the urease-producing bacteria liquid is 1.0-1.

9.

4. The preparation method according to claim 1, characterized in that: The formula of the culture medium is: 1-3g of yeast powder, 1-2g of tris(hydroxymethyl)aminomethane, and 0.5-1.5g of ammonium sulfate per 100ml of deionized water; The prepared culture medium needs to be sterilized at a temperature of 110-130°C for 20-40 minutes.

5. The preparation method according to claim 1, characterized in that: The synergistic bacterial strain can be selected from any one of Bacillus subtilis, Bacillus coli, and Pseudomonas aeruginosa; the mass ratio of the synergistic bacterial strain powder to deionized water is (4-10):

100.

6. The preparation method according to claim 1, characterized in that: In the step (3), the mass ratio of the calcium source, urea and deionized water is (4-6):(2-4):100; the calcium source is a soluble calcium salt, and the soluble calcium salt is any one of calcium nitrate, calcium acetate and calcium chloride.

7. The preparation method according to claim 1, characterized in that: The volume ratio of the original bacterial liquid to the binder is 1:(0.5-2).

8. The preparation method according to claim 1, characterized in that: The static condition of step (4) is soaking at 10-35° C. for 1-9 days.

9. A corrosion-resistant biomineralized film layer obtained by the method for preparing a corrosion-resistant biomineralized film layer according to any one of claims 1 to 8.

10. The use of a corrosion-resistant biomineralized film layer according to claim 9, characterized in that: The corrosion-resistant biomineralized film layer is used in the field of corrosion resistance of metal materials.

Citation Information

Patent Citations

  • Steel anti-corrosion method based on microbial technology

    CN112680733A

  • A rapidly synthesizable biomineralized coating, its preparation method and application

    CN116140165B

Cited By

  • Method for filling recombined bamboos by using biomineralization technology

    CN122275113A